The role of attention for the Simon effect - Hommel, B (Psychological research, 1993)
It has been claimed that spatial attention plays a decisive role in the effect of irrelevant spatial stimulus-response correspondence (i.e., the Simon effect), especially the way the attentional focus is moved onto the stimulus (lateral shifting rather than zooming). This attentional-movement hypothesis is contrasted with a referential-coding hypothesis, according to which spatial stimulus coding depends on the availability of frames or objects of reference rather than on certain attentional movements. In six experiments, reference objects were made available to aid spatial coding, which either appeared simultaneously with the stimulus (Experiments 1-3), or were continuously visible (Experiments 4-6). In contrast to previous experiments and to the attentional predictions, the Simon effect occurred even though the stimuli were precued by large frames surrounding both possible stimulus positions (Experiment 1), even when the reference object's salience was markedly reduced (Experiment 2), or when the precueing frames were made more informative (Experiment 3). Furthermore, it was found that the Simon effect is not reduced by spatial correspondence between an uninformative spatial precue and the stimulus (Experiment 4), and it does not depend on the location of spatial precues appearing to the left or right of both possible stimulus locations (Experiment 5). This was true even when the precue was made task-relevant in order to ensure attentional focusing (Experiment 6). In sum, it is shown that the Simon effect does not depend on the kind of attentional operation presumably performed to focus onto the stimulus. It is argued that the available data are consistent with a coding approach to the Simon effect which, however, needs to be developed to be more precise as to the conditions for spatial stimulus coding.